Self-fertilization depression in an introduced population of the land snail Rumina decollata (Linnaeus 1758) - Piza, Julia (2021)
Rumina decollata is a hermaphroditic terrestrial gastropod native to the Mediterranean region and introduced in many countries of the world. In Argentina, this species was first recorded in the 1980s. Although the current distribution is restricted to urban and peri-urban areas, it is expanding fast and is likely that it will colonize natural environments where it could affect native biodiversity and agriculture. Its high resistance to extreme climatic conditions and its omnivorous diet, together with its reproductive characteristics, favours the colonization of different environments. R. decollate has a high reproductive potential and facultative self-fertilization. The aim of this ongoing work is to study self-fertilization and its effect on fecundity (number of eggs per hatch) and fertility (proportion of eggs hatched) over two generations in an introduced population in Argentina. The parent generation (PG) consisted of 80 juveniles kept isolated until natural death. The 100% of the snails laid eggs by self-fertilization proving the high prevalence of this mode of reproduction in this species. In the F1 generation, 80 hatchlings from self-fertilization of the PG were randomly selected and assigned to different reproductive treatments: T1 (Forced self-fertilization: 40 isolated snails) and T2 (Self or cross-fertilization: 40 snails kept in pairs). The number of eggs per hatch and the proportion of eggs that hatched was significantly lower in the second generation of forced selfing (F1) than in PG. Considering F1, the number of eggs per hatch did not differ between reproductive treatments but the hatching proportion was significantly lower in forced self-fertilizers. The results obtained show evidence of self-fertilization depression in this species. Therefore, cross-fertilization may play a more important role than expected. Improving the knowledge of the biology and reproduction in R. decollata is crucial to determine its potential as an invasive species and to develop accurate control strategies.